Enterprise resource planning (ERP) system usage in Small and Medium-sized enterprises (SMEs) in Selangor / Nursyahida Zulkifli - Zulkifli, Nursyahida (2013)
The 2012 Budget announced by the Prime Minister of Malaysia indicated that small and medium enterprises (SMEs) continue to play an important role in the nation’s economy and are therefore, given sufficient allocation to sustain the various enterprise. As in all contemporary SMEs, the enabler for successful business ventures is through the use of information and communication technology (ICT). With premeditated information systems implementation, SMEs would be able to survive the demands of the current volatile economic conditions for competitive advantage. One such system is the Enterprise Resource Planning (ERP) for information mining in making strategic decision making. The ERP system provides the capability for fast, high quality data retrieval from large volumes of data for SME’s sustainability. Hence, the objectives of this study are; to examine the influence and relationship of the socio psychological factors toward the ERP system usage, and to investigate the effect of the socio psychological factors with the interaction of system complexity as moderator on the ERP system usage. The socio-psychological factors are perceived usefulness, rewards, perceived benefits and social influence. Consequently, the scope of this study is the SME’s in Selangor that are involved in the manufacturing industry. The methodology employed for this project is cross-sectional with purposive sampling technique for the identification of the units of analysis - the managers. Through a list provided by the SME Corporation (SME Corp) of Malaysia, five hundred SMEs that fit the pre-identified criteria were sent questionnaires for data collection. Prior to the actual data collection, a pilot study was undertaken to ensure the reliability and validity of the instrument. Subsequently, the study found that 43.8 percent of SMEs in Selangor have the ERP system experience with an average ERP system usage is between 1-5 years. Moreover, the perceived benefits (r=0.23, p<0.05) and social influence (r=0.35, p<0.01) were significantly correlated with the ERP system usage and the social influence (P=0.41, p<0.05) was the most influential socio psychological factor towards the ERP system usage. In addition, the findings showed that all the socio psychological factors not significantly moderated by the system complexity in influencing the ERP system usage. It means that the system complexity does not act as an independent variable and moderating variable in this study because it is not significant due the significant value, p, is greater than 0.05. The findings indicated that not all SMEs in the manufacturing sector within Selangor are embracing ERP system, let alone using the ERP system to aid their decision making process. A change champion from an established SME that has successfully been utilizing ERP be recruited to promote ERP system for all SMEs. Employees should be given the right training on ERP system use, who in turn will train other staff reap the benefit of a customized computer system. Once the perception that the system is easy to use, is useful, and is advantageous to them, the organization will be well on the way to a profitable business quantum and achieve better returns of investment. The implication from non-usage of ERP system will negatively impact the SMEs ability to compete at both the local and international level, hence, internal management and organizational matters, particularly leadership and resilience must be enhanced.